Design of Dual Band Circular Microstrip Patch Antenna with Slot for WLAN Applications - Nageswara Rao, L; Ramesh, B; Santhosh Kumar, V (International Journal of Engineering and Technology, 2018)
A composite double - band circular microstrip patch (MPA) with space opening for WLAN is intended. An investigated configuration is feasible for WLAN applications. An investigated configuration includes the circular patch and π - space resonator. The compact in the antenna size for the lower band is attained by adopting a π – shaped opening space on the ground plane. By balancing the model specifications, a circular patch resonator act at the primary band (5.2 GHz) and the π -  space slot act at the secondary band (2.4 GHz), while using the substrate substantial FR4 whichever carry dielectric constant of 4.4 (ɛr). The arranged antenna configuration has small in size, less weight, reduced cost and acceptable isolation. Designed structure presents the return loss less than -10 B and it is indicated with significant impedance matching, improved radiation pattern and good VSWR around 1 over the working bands. The investigated configuration is simulated and analyzed with HFSS.